Performance Assessment of a Multi-Generation System Based on Organic Rankine Cycle - Sharifishourabi, Moslem; Ratlamwala, Tahir Abdul Hussain; Alimoradiyan, Hamed; Sadeghizadeh, Ehsan (Springer, 2017)
In this paper, a new multi-generation system is proposed and analyzed through energy and exergy. The new system uses solar power as its energy source and delivers six beneficial productions for the residential sector, such as hotels. These outputs include hot water, electricity, heating, cooling, dry air, and hydrogen production. The effects of some factors such as the inlet and outlet temperature of turbine and ambient temperature on the performances of the system are evaluated. The results show that the energetic COP of the absorption chiller cycle is found to be 60%, whereas the exergetic COP of the absorption system is found to be about 10%. Also, energetic and exergetic efficiency of the organic Rankine cycle is determined to be 8 and 27%, respectively. Moreover, overall energetic and exergetic efficiency of the system is found to be 70 and 53%, respectively.
Keywords: Organic Rankine cycle; Multi-generation System; Energy; Exergy; Efficiency